Drying of Carrot Slices Under Infrared Radiation: Effect of Pretreatments on Drying Characteristics, Rehydration Ratio, and Color Parameters - Soydan, M.; Doymaz, I. (WILEY, 2026)
This study investigates the assessment of drying parameters for yellow carrots by comparing the effects of various pre-treatments and an infrared power setting of 62 W on drying kinetics, color stability, and rehydration characteristics. Pre-treatments included steam blanching (SB) at 100 degrees C, water blanching (WB) at 90 degrees C, and immersion in 2% citric acid (CA) solution for 2 min, along with a control group. Infrared drying reduced the initial moisture content of 6.95 kg water/kg dry matter to 0.11 kg water/kg dry matter, with drying durations of 120 min for SB, 130 min for WB, 150 min for CA, and 160 min for the control. The implementation of pretreatment techniques significantly enhanced the drying kinetics, expediting moisture removal by altering the microstructural properties of carrot slices and promoting more efficient water migration. Pre-treatments influenced color retention and rehydration capacity significantly. CA-treated samples exhibited superior color preservation, while SB-treated samples achieved the highest rehydration ratio. The control group showed inferior performance in all quality parameters. The measured diffusion coefficients fell within a range of 1.53 x 10- 9-1.87 x 10- 9 m(2)/s. SB-treated specimens yielded the maximum coefficient, signifying superior moisture transfer capacity. The Midilli & Kucuk and the Aghbashlo et al. models were identified as the most suitable for characterizing drying behavior. Steam blanching (SB) proved to be an exceptionally efficient pre-treatment method, owing to its remarkable ability to penetrate carrot tissue more effectively. This process enhanced moisture diffusion by facilitating the expansion of pores, thereby creating pathways for water trapped within the carrot slices to escape more readily. By maintaining the structural integrity of both intercellular and intracellular spaces during the pre-treatment process, SB substantially minimized drying durations, improved rehydration capacity, and more effectively retained the natural color of carrot slices in comparison to water blanching. SB also minimized structural and textural degradation, as shorter drying periods and reduced heat exposure preserved the carrot slices' integrity and appearance. These findings highlight the potential of steam blanching as a pre-treatment to enhance drying efficiency and product quality, underscoring its value for industrial applications in carrot drying.
Keywords: color retention; drying kinetics; infrared drying; pre-treatments; rehydration capacity; MOISTURE DIFFUSIVITY; KINETICS; EQUILIBRIUM; DEGRADATION; QUALITY; ENERGY; Thermodynamics